Who starts with open source? Institutional choice of start-ups in the German ICT sector - Michael Fritsch; Sebastian von Engelhardt (Friedrich Schiller University Jena and Max Planck Institute of Economics, 2010)
We analyze the characteristics of new businesses in the German ICT industry, distinguishing them based on their choice between two IPR regimes: open source software (OSS) or closed source software (CSS). The share of new firms with an OSS-based business model has increased considerably over the last several years. OSS-based firms tend to be smaller (in terms of staff and capital) and experience less shortages of capital. Only older cohorts of OSS-intensive start-ups had more difficulty than their CSS counterparts in convincing potential financiers of their viability, indicating that OSS business models are now well established. We find no evidence that the lower entry barriers for OSS firms are particularly attractive to start-ups with low human capital endowment or to necessity-motivated entrepreneurs.
Keywords: D02; L17; L26; L86; 330; new business formation; institutions; open source intellectual property rights; software industry; Unternehmensgründung; Open Source; Geschäftsmodell; IT-Industrie; Softwareindustrie; Deutschland